Signalization and Stimulus-Substitution in Pavlov’s Theory of Conditioning - García-hoz, Victor (The Spanish Journal of Psychology, 2003)
The concept of conditioning as signalization proposed by Ivan P. Pavlov (1927, 1928) is studied in relation to the theory of stimulus-substitution, which is also attributed to him. In the so-called theory of stimulus-substitution a distinction must be made between an empirical principle of substitution and an actual theory of substitution, which can adopt different forms. The Pavlovian theory of substitution—which conceives substitution as a substitution of the unconditioned stimulus (US) by the conditioned stimulus (CS) in the activation of the representation of the former—can be understood as an explanation or model of signalization. Signalization and substitution are answers to different questions, and the level of analysis to which signalization corresponds, is that which concerns the nature of conditioning as an operation of the animal in the environment.